Beyond Structural Listening? Postmodern Modes of Hearing - Dell'Antonio, Andrew (Berkeley, CA University of Chicago Press, 2004)
In a highly influential essay, Rose Rosengard Subotnik critiques "structural listening" as an attempt to situate musical meaning solely within the unfolding of the musical structure itself. The authors of this volume, prominent young music historians and theorists writing on repertories ranging from Beethoven to MTV, take up Subotnik's challenge in what is likely to be one of musical scholarship's intellectual touchstones for many years to come. Original, innovative, and sophisticated, their essays explore not only the implications of the "structural listening" model but also the alternative listening strategies that have developed in specific communities, often in response to twentieth-century Western music.
Keywords: Music philosophy and esthetics; Listening; Postmodernism